The Effectiveness of Project-Based Learning (Pjbl) in Enhancing Students’ Writing Skills - Ramdania, Nofa Elok; Krisbiantoro, Benny; Soali, Muhammad (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This study aimed to assess the effectiveness of Project-Based Learning (PjBL) in enhancing the writing skills of grade XI students at SMA Muhammadiyah 1 Purwokerto. The study used a quasi-experimental design with an experimental group taught using PjBL and a control group using Direct Instruction (DI). The sample consisted of 59 students, and data were collected through pre-test and post-test measuring their argumentative writing skills. The results indicated that the experimental group showed a significant improvement in their writing skills, with an average increase of 10.24 points (Δ = 10.24) compared to the control group's 6.13 points (Δ = 6.13). The independent t-test results demonstrated a significant difference between the two groups at the 0.004 level. These findings suggest that PjBL is more effective than DI in enhancing students' writing abilities, fostering creativity, and encouraging critical thinking. The study highlights the importance of implementing innovative, student-centered approaches in writing instruction.